2020
DOI: 10.1101/2020.06.17.156752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation bias shapes gene evolution inArabidopsis thaliana

Abstract: Classical evolutionary theory maintains that mutation rate variation between genes should be random with respect to fitness 1-4 and evolutionary optimization of genic mutation rates remains controversial 3,5 . However, it has now become known that cytogenetic (DNA sequence + epigenomic) features influence local mutation probabilities 6 , which is predicted by more recent theory to be a prerequisite for beneficial mutation rates between different classes of genes to readily evolve 7 . To test this possibility, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…It has recently been shown that coding region mutation rates as measured prior to the effect of natural selection are significantly lower in genes where mutations are more likely to be deleterious ( Monroe et al, 2020 ). Mutations are more likely to be deleterious and less likely to be fixed in highly conserved proteins, which are by definition more common in slowly evolving proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that coding region mutation rates as measured prior to the effect of natural selection are significantly lower in genes where mutations are more likely to be deleterious ( Monroe et al, 2020 ). Mutations are more likely to be deleterious and less likely to be fixed in highly conserved proteins, which are by definition more common in slowly evolving proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that mutation saturation as measured by the overlap ratio method has been largely overlooked ( Huang, 2012 ; Yuan et al, 2017 ), in contrast to the long noted LBA. As mentioned above, it appears that the inherent mutation rates are different between fast and slowly evolving proteins as determined by studying the rate of fixed substitutions ( Monroe et al, 2020 ). We can thus infer that if the rate difference is large enough, slowly evolving genes should be used in phylogenetic inferences because they would be less likely to reach mutation saturation.…”
Section: Discussionmentioning
confidence: 99%
“…The genome-wide epimutation rates for CG regions were 5 orders of magnitude higher than this mutation rate. This finding indicates that, similarly to single Cs, region-level epimutations occur independently of genetic mutations and provide a separate source of genome evolution and diversity (Monroe et al, 2020). Our results have major implications for understanding how linkage disequilibrium (LD) between genetic variants and differentially methylated regions (DMRs) evolves over time, and substantiate the need for methylation-based epigenome-wide association studies (EWAS) in plants.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, it could be very complex to define site-specific preferences in a meaningful way. It has recently been shown that coding region mutation rates as measured prior to the effect of natural selection are significantly lower in genes where mutations are more likely to be deleterious (Monroe et al 2020). Mutations are more likely to be deleterious and less likely to be fixed in highly conserved proteins, which are by definition more common in slowly evolving proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed studying the rate of fixed substitutions (Monroe et al 2020). We can thus infer that if the rate difference is large enough, slowly evolving genes should be used in phylogenetic inferences because they would be less likely to reach mutation saturation.…”
Section: Discussionmentioning
confidence: 99%